Security Issues in the Computerized Land Registration System in Malaysia: An Overview: (Individu Autisme dan Perlakuan Melanggar Undang-undang) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Individuals with autism experience complex neuro-developmental disorders in early childhood or neuro-development disturbances, as a result of which they exhibit unusual behaviours that are usually beyond their control. Despite the increasing number of individuals with autism in Malaysia, the general public is still lacking in knowledge regarding behaviours of individuals with autism. The actions of individuals with autism can at times be categorized as criminal or syariah offences. This article aims to discuss the consequence of behaviours of those individuals that result in them breaking laws. The focus of this discussion is also to identify the types of illegal offences committed by teenagers with autism. The methods of data collection are through document analysis and semi-structured interviews with teachers from a non-governmental organization that was established to conduct intervention programmes for autistic individuals. The data gathered was analysed descriptively and presented according to relevant themes. The study found that individuals with autism have their own behaviours which exposes them to committing criminal offences. These behaviours include difficulties to adapt in new places and environments, understanding verbal and non-verbal social interaction, an unusually deep interest in or obsession with certain subjects. These behaviours are found to be capable of influencing them to commit criminal offences such as murder, arson, sexual offences as well as cybercrime.Keywords: ASD, autism, criminal offences, sexual behavior